Causes of anomalous mineralogical diversity in the Periodic Table. (2nd January 2018) - Christy, Andrew G.
Abstract: When crustal abundance ( A, measured in atomic parts per million) of a chemical element is plotted vs. number of mineral species in which that element is an essential constituent ( S ), a significantly positive correlation is obtained, but with considerable scatter. Repeated exclusion of outliers at the 90% confidence level and re-fitting leads, after the sixth iteration, to a steady state in which 40 of the 70 elements initially considered define a trend with log S = 1.828 + 0.255 log a ( r = 0.96), significantly steeper than the original. Three other methods for reducing the effect of outliers independently reproduce this steeper trend. The 'diversity index' D of an element is defined as the ratio of observed mineral species to those predicted from this trend. D separates elements into three groups. More than half of the elements (40 of 70) have D = 0.5–2.0. Apart from these 'typical' elements, a group of 15 elements (Sc, Cr, Ga, Br, Rb, In, Cs, La, Nd, Sm, Gd, Yb, Hf, Re and Th) form few species of their own due to being dispersed as minor solid solution constituents, and a hitherto unrecognized group of 15 elements are essential components in unusually large numbers of minerals. The anomalously diverse group consists of H, S, Cu, As, Se, Pd, Ag, Sb, Te, Pt, Au, Hg, Pb, Bi and U, with Te and Bi by far the most mineralogically diverse elements ( D = 22 and 19, respectively). Possible causes and inhibitors of diversity are discussed, with reference to atomic size, electronegativity and Pearson softness, and particularly outer electronic configurations that result in distinctive stereochemistry. The principal factors encouraging mineral diversity are: (1) Particular outer electronic configurations that lead to a preference for unique coordination geometries, enhancing an element's ability to form distinctive chemical compounds and decreasing its ability to participate in solid solutions. This is particularly noteworthy for elements possessing geometrically flexible 'lone-pair cations' with an s 2 outer electronic configuration. (2) Siderophilic or chalcophilic geochemical behaviour and intermediate electronegativity, allowing elements to form minerals that are not oxycompounds or halides. (3) Access to a wide range of oxidation states. The most diverse elements can occur as anions, native elements and in more than one cationic valence state.